fAlert : Um sistema android para monitoramento de quedas em pessoas com cuidados especiais - Piva, Leonardo Sabadini; Ferreira, Andressa Bezerra; Andrade, Rossana Maria de Castro; Braga, Reinaldo Bezerra (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2014)
This paper presents a system for detection and warning of falls for people with special care needs, using real-time evaluated data from accelerometer and magnetometer sensors of mobile devices with android operating system, using algorithms to detect patterns of falls, device position and voice recognition to determine a possible fall. We performed 240 tests in a young healthy user using the Samsung Galaxy S3 I9300 device strapped to his chest in order to ensure efficiency in detecting falls.